Pengaruh Size, Leverage, Profitability, Dan Capital Intensity Ratio Terhadap Effective Tax Rate (Etr) - Vika Rahmawati; Titik Mildawati (Jurnal Riset Keuangan dan Akuntansi, 2020)
This study aims to examine the effect of size, leverage, profitability, and capital intensity ratio on the effective tax rate (ETR). This type of research is quantitative research. The sample of this study amounted to 39 consisting of 13 LQ45 companies listed on the Indonesia Stock Exchange (IDX) from 2015 - 2017. The statistical test tools in the form of the SPSS program were used for classical assumption tests and multiple regression analysis. The results of this study indicate that the size does not affect the effective tax rate (ETR) because the company has not utilized its assets to the full. Profitability has a positive effect on effective tax rate (ETR) because large companies are able to pay their taxes according to their income and capital intensity ratios have a positive effect on the effective tax rate (ETR) due to asset contributions of only a few percent and each year depreciation is used for the tax deduction the value is the same. While leverage has a negative effect on effective tax rate (ETR) because large  companies have debts that generate interest costs, the interest costs are used to reduce the company's net income. Keywords: Size, Leverage, Profitability, Capital Intensity Ratio, Effective Tax Rate